ANALISA PENULANGAN KONSTRUKSI GEDUNG SATU BASEMEN EMPAT LANTAI - Imaduddin, Muhammad; Arfan, Muhammad; Hariyanto, Agus (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
Based on the artifact drawing in the appendix, it discusses structural planning where only drawings are produced in planning and there is no reinforcement plan which is an important element in the construction of a building in order to produce a strong, safe and economical building. Therefore, the author discusses the reinforcement of the structure. To achieve the planning objectives, structural planning must follow the regulations set by the government in the form of the Indonesian National Standard (SNI). Planning of the building that has been determined so that the strength and safety factors of the building can be achieved and there is no collapse in the planned building. The results of the analysis of a four-story basement office building from the calculations obtained the same results in calculations using the SAP 2000 and SNI programs 03-2847-2002, therefore the reinforcement obtained is accurate, namely the results of the SAP 2000 and SNI programs 03-2847-2002 . The results of planning a four-storey office building from several planned variations obtained a total net concrete area, namely variation 1 of 14800.96 cm², variation 2 of 15172.1 cm², variation 3 of 11297.69 cm² and variation 4 experiencing structural failure. From these results it can be concluded that the safe and economical variations of beams, columns are variation 3 where the dimensions are B1 (30 cm x 40 cm), B2 (15 cm x 25 cm), K1 (50 cm x 50 cm), K2 (45 cm x 45 cm), K3 (40 cm x 40 cm), K4 (35 cm x 35 cm)